INOVASI MODEL PEMBELAJARAN MELALUI PROJECT-BASED LEARNING: MENGGALI POTENSI KREATIVITAS SISWA - Wicaksono, Fachri; Komalasari, Kokom; Wiyanarti, Erlina (JEMBA, 2023)
Rapid world developments and changes in society demand an innovative and relevant learning approach to improve the quality of student education. In this context, the Project Based Learning (PjBL) model offers interesting potential for increasing student creativity through project-based learning which emphasizes students' active involvement in planning and implementing projects that are relevant to the real world. Therefore, this research aims to identify students' perceptions of the Project Based Learning (PjBL) Model and the extent to which its application can influence student creativity. The research method used was a quantitative approach with data collection techniques used with instruments in the form of questionnaires, as well as data analysis through simple linear regression using SPSS Statistics 20. The results of the research showed that students had a positive perception of the Project Based Learning (PjBL) Model. They also have a supportive view of student creativity at the school. Apart from that, the use of the Project Based Learning (PjBL) model significantly influences students' creativity, which means that this learning model can increase students' creativity in the learning process in the 21st century.